Evaluation of Anti-bacterial Effect of Rhamnus Prinoides Mouthwash on Streptococcus Mutans Count in a group of Orthodontic Patients with Gingivitis (Mustansiria Dental Journal, 2022)
Aim of the study: This study was conducted to evaluate the antibacterial effect of Rhamnus prinoides  mouthwash against Streptococcus mutans in a group of  orthodontic patients with gingivitis, and to compare the gingival index before and 3 weeks after using Rhamnus Prinoides mouthwash and placebo 2 times daily for study and control group respectively.Materials and methods: Rhamnus Prinoides mouthwash was extracted from plant leaves, filtered, then it was mixed with ethanol after being dried. The anti-bacterial effect was evaluated by measuring the streptococcus mutans count before and after 3 weeks of using Rhamnus Prinoides mouthwash and placebo in study and control group respectively.Results: Rhamnus Prinoides mouthwash demonstrated an anti-bacterial effect by significantly reducing the mean streptococcus mutans count from 14.23*10-5±7.67 (CFU/ml) to 0.45*10-5±0.28 (CFU/ml) in study group. While in control group mean streptococcus mutans count significantly increased from 13.79*10-5±11.11 (CFU/ml)  to 30.22*10-5±33.57 (CFU/ml). The mean gingival index found to change significantly from the moderate type at the base line (gingival index = 1.53± 0.26) to mild type on the third week (gingival index= 0.97±0.007 ) in study group, while in control group it remained with moderate type from the base line visit (gingival index= 1.44±0.16)  to the third week (gingival index= 1.46±0.16).Conclusion: Rhamnus Prinoides mouthwash exhibited a significant anti-bacterial activity by reducing the streptococcus mutans count, and thus it can be considered as a  promising oral health care product in the future.